2020
DOI: 10.1167/iovs.61.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Agrin Promotes Limbal Stem Cell Proliferation and Corneal Wound Healing Through Hippo-Yap Signaling Pathway

Abstract: Purpose To investigate the effect and mechanism of Agrin on limbal stem cell proliferation and corneal wound healing. Methods Limbal stem cells were isolated and treated with different concentrations of Agrin. CCK-8 and cell proliferation markers (Ki67 and pH3) were detected to evaluate cell numbers or proliferative potential of limbal stem cells. The corneal epithelium wound model was induced by debridement of central corneal epithelial, and the effects of Agrin on lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Previous studies on decellularized limbal tissue provided little detailed examinations of ECM components [ 20 , 21 ]. Agrin, a heparin sulfate proteoglycan that promotes LEPC proliferation and corneal wound healing [ 41 ], is highly expressed in the limbal region and its expression declines towards the central cornea [ 25 ]. Agrin was preserved in the DHL scaffolds of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on decellularized limbal tissue provided little detailed examinations of ECM components [ 20 , 21 ]. Agrin, a heparin sulfate proteoglycan that promotes LEPC proliferation and corneal wound healing [ 41 ], is highly expressed in the limbal region and its expression declines towards the central cornea [ 25 ]. Agrin was preserved in the DHL scaffolds of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In the ocular surface, agrin is highly expressed in the limbal regions partially colocalized with limbal stem cells (ABCG2 and p63-positive cells), and the expression of agrin decreases toward the conjunctiva (weakly expressed) and central cornea (absent or weakly expressed) ( Figure 4 ) ( Schlötzer-Schrehardt et al, 2007 ). A recent report has shown that agrin promotes limbal stem cell proliferation and corneal wound healing via the Hippo-Yap signaling pathway ( Hou et al, 2020 ). Conditional knockout of agrin in the cornea could potentially help further our understanding of the role of agrin in supporting limbal stem cells.…”
Section: Heparan Sulfate Proteoglycans (Hspgs)mentioning
confidence: 99%
“…DIANA-TarBase and microT-CDS algorithms (genes union function) were used to identify experimentally supported and predicted miRNA/target-mRNA interactions, respectively, as well as significant KEGG pathways, in which target genes were involved ( Table 2 and Table 3 ). Among them emerged the ECM-receptor interaction and the focal adhesion pathways, already described in cornea homeostasis and normal physiological functions [ 27 ], corneal epithelial cell motility [ 28 ], neovascularization [ 29 ] and adhesion [ 30 , 31 ], the Hippo signaling pathway, playing a role in limbal cell proliferation, corneal wound healing and regeneration [ 32 , 33 ] and, as expected, the Neurotrophin signaling pathway. The latter was considered for more in-depth analysis: sixty and fifty genes, targeted by 18 and 16 out of 21 miRNAs (miR-337-5p, mir-34a-3p, mir-1227-3p did not show any target gene) were detected by DIANA-TarBase and microT-based analysis, respectively ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%